An Experimental Investigation on the Influence of Copper Ageing on Flow Boiling in a Copper Microchannel. Issue 4 (21st February 2020) - Jayaramu, Prasanna; Gedupudi, Sateesh; Das, Sarit K.
Abstract: The study reports the experimental investigation on the influence of copper ageing on flow boiling heat transfer and pressure drop in copper microchannels of two different hydraulic diameters, 0.324 and 0.658 mm. Experiments have been conducted for different time intervals between the experimental runs. A reduction in the two-phase heat transfer coefficient was noticed with time, possibly due to the growth of oxidation layer. Energy-dispersive X-ray spectroscopy analyses of the fresh sample and the sample after the experiments indicated the growth of oxidation layer. Confocal microscope images and three-dimensional roughness profiles obtained using an optical profilometer also indicated a change in the surface texture. Deterioration in two-phase heat transfer coefficient was attributed to the increased surface wettability caused by the oxidation. The rate of reduction in heat transfer coefficient was higher for higher heat fluxes and smaller hydraulic diameter. A small increase in two-phase pressure drop was also noticed. Possible sources of oxidation were discussed in the study. The study underlines that the copper ageing factor be taken into account for the design and operation of two-phase microchannel heat sinks with copper substrate.